Diagnosis Komunitas Dalam Upaya Menstabilkan Angka Kunjungan Diabetes Melitus Tipe 2 Di Desa Kresek, Kabupaten Tangerang - Laura, Gabrielle; Rahmawati, Eny; Saloko, Glenn Javier Dannari; Catherine, Michelle; Ferdianto, Ferdianto (Syntax Corporation, 2025)
Based on the 2023 Indonesian Health Survey, the prevalence of Diabetes Mellitus (DM) in the population aged ≥15 years reached 11.7%. In Tangerang Regency, the prevalence of DM reached 1.9%. In 2024, 1,940 visits were recorded in 10 villages in the Kresek Health Center's working area, with Kresek Village having the highest (471 visits, 24.3%). Visits increased from 117 (6.0%) in February to 217 (11.2%) in November, then decreased to 167 (8.6%) in December. Stabilize the number of Type 2 DM visits in the Kresek Health Center work area by increasing public understanding of diabetes and encouraging awareness of the importance of routine blood sugar checks. Community diagnosis uses the Blum paradigm for problem identification, the non-scoring technique (Delphi) method for problem prioritization, and fishbone diagrams for root cause problems. Interventions were carried out through counseling and fasting blood sugar (GDP) checks, with evaluation using pre-tests and post-tests. The increase in participants' knowledge from pre-test to post-test was 76.3% (23 out of 30 participants achieved a score of ≥70). The GDP examination found 3 people with results of ≥126 mg/dL who were referred for follow-up examination. The intervention succeeded in increasing public knowledge about DM and awareness of the importance of routine blood sugar checks at health centers to stabilize the number of visits.